Change of Color and Growth of Koi Fish (Cyprinus rubrofuscus) with Addition of Seaweed Extract (Kappaphycus alvarezii) on Feeds - Syamsinar, Syamsinar; Jamaluddin, Jamaluddin; Indrayani, Indrayani (Journal of Agroscience Indonesia, 2023)
Seaweed is a marine plant belonging to the benthic macroalgae which lives a lot attached to the bottom of the waters. Seaweed has three main types of pigments, namely chlorophyll, carotenoids, and phycobiliproteins. The content of carotenoids is one of the most important groups of natural pigments which functions to pigment skin color (scales). Carotenoids also affect fish growth, with the availability of carotenoids in the fish's body, raw materials are available to be synthesized into important compounds needed by fish. This study aimed to analyze the effect of adding seaweed extract to feed on the brightness and growth of koi fish. This study is an experimental study using a completely randomized experimental design (CRD) consisting of 4 treatments with 3 repetitions. The treatments consisted of treatment K (100% commercial feed), A (7% seaweed extract, 93% commercial feed), B (5% seaweed extract, 95% commercial feed), C (3% seaweed extract, 97% commercial feed). Each treatment was observed on color brightness and growth (absolute weight, SGR), feed utilization (FCR and EPP), water quality, temperature, pH, and ammonia. The data was processed using SPSS version 24 program with Tukey HSD analysis. The results of this study showed that the administration of seaweed extract with different concentrations affected the color brightness and growth of koi fish (Cyprinus rubrofuscus). Where treatment A was the best treatment for color brightness 13.87, and treatment C was the best treatment for growth with absolute weight growth of 2.5 grams, SR 90%, FCR 1.7%, EPP 58%.